Inhibition of Growth and Induction of Apoptosis in Fibrosarcoma Cell Lines by Echinophora platyloba DC: In Vitro Analysis - Fatemeh Zare Shahneh; Samira Valiyari; Abbas Azadmehr; Reza Hajiaghaee; Saeid Yaripour; Ali Bandehagh; Behzad Baradaran (Advances in Pharmacological Sciences)
Echinophora platyloba DC plant (Khousharizeh) is one of the indigenous medicinal plants which is used as a food seasoning and medicine in Iran. The objective of this study was to examine the in vitro cytotoxic activity and the mechanism of cell death of crude methanolic extracts prepared from Echinophora platyloba DC, on mouse fibrosarcoma cell line (WEHI-164). Cytotoxicity and viability of methanolic extract was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and dye exclusion assay. Cell death ELISA was employed to quantify the nucleosome production result from nuclear DNA fragmentation during apoptosis and determine whether the mechanism involves induction of apoptosis or necrosis. The cell death was identified as apoptosis using terminal deoxynucleotidyl transferase- (TdT-) mediated dUTP nick end labeling (TUNEL) assay. Our results demonstrated that the extract decreased cell viability, suppressed cell proliferation, and induced cell death in a time- and dose-dependent manner in WEHI-164 cells (IC50 = 196.673 ± 12.4 μg/mL) when compared with a chemotherapeutic anticancer drug, Toxol. Observation proved that apoptosis was the major mechanism of cell death. So the Echinophora platyloba DC extract was found to time- and dose-dependently inhibit the proliferation of fibrosarcoma cell possibly via an apoptosis-dependent pathway.